2014
DOI: 10.5539/gjhs.v6n6p163
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone Versus Risperidone Plus Sodium Valproate for Treatment of Bipolar Disorders: A Randomized, Double-Blind Clinical-Trial

Abstract: Objective:This study compared the efficacy of risperidone monotherapy with risperidone plus valproate in bipolar I disorder, manic phase. Some studies showed the efficacy of risperidone monotherapy in the treatment of bipolar disorder, so we examined this effectiveness in this clinical-trial study.Method:This 7-week, randomized, single-blind study included 48 bipolar I inpatients manic phase without psychotic features divided in risperidone group (n = 23) and risperidone plus sodium valproate group (n = 25). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…After the traditional mood stabilizer yields sufficient therapeutic benefit, risperidone may be tapered in order to lower the risks of weight gain or metabolic side effects that were identified in the primary report of the TEAM study 16 . Although the sample was very small, a recent study in adults showed improvement in bipolar depression happened more quickly with a combination of risperidone and valproic acid verus risperidone alone 26 . Similar to our study, this group found that despite the early improvement, at study end, both groups had the same degree of improvement.…”
Section: Discussionmentioning
confidence: 98%
“…After the traditional mood stabilizer yields sufficient therapeutic benefit, risperidone may be tapered in order to lower the risks of weight gain or metabolic side effects that were identified in the primary report of the TEAM study 16 . Although the sample was very small, a recent study in adults showed improvement in bipolar depression happened more quickly with a combination of risperidone and valproic acid verus risperidone alone 26 . Similar to our study, this group found that despite the early improvement, at study end, both groups had the same degree of improvement.…”
Section: Discussionmentioning
confidence: 98%
“…In patients refractory to lithium, valproate, or carbamazepine, it is beneficial to add haloperidol, olanzapine, quetiapine, aripiprazole, or asenapine ( Szegedi et al, 2012 ) ( Sachs et al, 2002 , 2004 ; Tohen et al, 2002b ; Yatham et al, 2007 ; Vieta et al, 2008b ) but not ziprasidone, topiramate, risperidone, or paliperidone ( Roy Chengappa et al, 2006 ; Berwaerts et al, 2011 ; Sachs et al, 2012a , 2012b ; Moosavi et al, 2014 ). One study that used a mixed population with some patients entering after a minimum of 2 weeks of mood stabilizer therapy, and others starting a mood stabilizer and risperidone in parallel, provided inconclusive data for risperidone ( Yatham et al, 2003 ) as the results were likely confounded by the effects of carbamazepine on serum levels of risperidone.…”
Section: Efficacy Datamentioning
confidence: 99%
“…Of the remaining 29 trials, 5 were excluded from the primary 24-week analysis because they were either 12-week trials (n = 3, EXXELERATE, 20 REALISTIC, 21 and Lan 22 ) or were disconnected from the network due to switching or rerandomization prior to the 24-week time point (n = 2, Abe 23 and CNTO 148 24 ). Five additional trials were excluded as either all treatment arms were monotherapy (n = 3, ADACTA, 25 SATORI, 26 and MONARCH 27 ) or because excluding monotherapy arms only left a single treatment arm (n = 2, ACT-RAY 28 , 29 and JESMR 30 ) ( Supplementary Material, Figure S1 ). Furthermore, for the purpose of this analysis, treatment arms investigating monotherapy or treatment doses that were out of scope were excluded from trials with more than two treatment arms (eg, ORAL SCAN 31 and ORAL STANDARD 32 [TOFA 10 mg + MTX]; ORAL STRATEGY 13 [TOFA 5 mg monotherapy]; Edwards 33 [RTX 1000 mg monotherapy]; SERENE 34 [RTX 500 mg + MTX]; and MOBILITY 18 [SARI 150 mg + MTX]).…”
Section: Resultsmentioning
confidence: 99%